Ranogotički reljef anđela "Navještenja", Bale u Istri - Marković, Predrag (Array, 1997)
On the site of the ancient parish chuurch of Bale in Istria, wich haad been rebuilt several times, a new church was built at the end of the nineteenth century. This led to the dismantling of its old Gothic portal and the distribution of its parts in the interior of the new church. The marble statue of the angel of the Annunciation wich had been orginaly been placed at the pointed crown of the portal's arch has been almost compleetly neglected by specialist altought it is superiorin execution to the relief of the Ressurected Christ orginaly in the lunette of the portal. The somewhat stiff attitude and the summary modeling of this figure (presented down to the waist) reflect the retarded influence of the Venetian Trecento sdculpture, especialy in the rich vegetable ornament of the console, from wich the bust emerges. Judging from the charatheristic grape-like fruit motif and the points of fleshy leaves, this ornament is related to a similar vegetable ornament on the gallery capital of the Franciscan monastery cloister in Pula, as well as to the capitals of two columns flanking the side entrance to the Comunal Palace atrium in Pula dated by inscription in 1431.Discusing this specific type of vegetable architectural decoration in the early fifteenth century, the autor futher relates it to some analogous solutions found in the eastren Adriatic coast as well as the genesis of the grape-like motif. In the contex of the regional sculpture of Istria in the second quarter of fifteenth century, the Angel of Anunnciation in Bale, along with the Pula capitals, can be attributed to a Venetian artist of average artistic potential.